Focal drug administration via heparin-containing cryogel microcarriers reduces cancer growth and metastasis. (1st October 2020) - Newland, Ben; Varricchio, Carmine; Körner, Yvonne; Hoppe, Franziska; Taplan, Christian; Newland, Heike; Eigel, Dimitri; Tornillo, Giusy; Pette, Dagmar; Brancale, Andrea; Welzel, Petra B.; Seib, F. Philipp; et al.
Graphical abstract: Highlights: Heparin-based microcarriers load and release drugs by electrostatic attraction. Doxorubicin preferentially binds to the heparin component of the microcarrier. Doxorubicin release lasted 42 days. Drug loaded microcarriers reduced breast cancer tumor growth in vivo . Abstract: Developing drug delivery systems that release anticancer drugs in a controlled and sustained manner remains challenging. We hypothesized that highly sulfated heparin-based microcarriers would allow electrostatic drug binding and controlled release. In silico modelling showed that the anticancer drug doxorubicin has affinity for the heparin component of the microcarriers. Experimental results showed that the strong electrostatic interaction was reversible, allowing both doxorubicin loading and a subsequent slow release over 42 days without an initial burst release. The drug-loaded microcarriers were able to reduce cancer cell viability in vitro in both hormone-dependent and highly aggressive triple-negative human breast cancer cells. Focal drug treatment, of an in vivo orthotopic triple-negative breast cancer model significantly decreased tumor burden and reduced cancer metastasis, whereas systemic administration of an equivalent drug dose was ineffective. This study proves that heparin-based microcarriers can be used as drug delivery platforms, for focal delivery and sustained long-term drug release.